2015
DOI: 10.1364/boe.6.000297
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and morphological studies in Japanese medaka with ultra-high resolution optical coherence tomography

Abstract: Abstract:We propose ultra-high resolution optical coherence tomography to study the morphological development of internal organs in medaka fish in the post-embryonic stages at micrometer resolution. Different stages of Japanese medaka were imaged after hatching in vivo with an axial resolution of 2.8 µm in tissue. Various morphological structures and organs identified in the OCT images were then compared with the histology. Due to the medaka's close resemblance to vertebrates, including humans, these morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Recently, the UHR-SD-OCT imaging of paralyzed medaka fish has been reported using combined SLD. 22) In conclusion, high-speed UHR OCT was demonstrated in the 800 nm wavelength region. As the broadband light source, we used a high-power Gaussian-like-shaped coherent SC with a bandwidth of 105 nm.…”
mentioning
confidence: 79%
“…Recently, the UHR-SD-OCT imaging of paralyzed medaka fish has been reported using combined SLD. 22) In conclusion, high-speed UHR OCT was demonstrated in the 800 nm wavelength region. As the broadband light source, we used a high-power Gaussian-like-shaped coherent SC with a bandwidth of 105 nm.…”
mentioning
confidence: 79%
“…These vessel diameters corresponded to the inner diameter and were larger than our minimum diameter, with an average of 5.6 µm (7.1 ± 1.5 µm) ( Table 1). In a medaka brain, Gladys et al 28 showed only medaka's morphological features in vivo, without the delineation of the cerebral microvessels. www.nature.com/scientificreports/ To accomplish the intact in vivo high-resolution imaging of microvasculature, we established a special samplemanipulation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…These vessel diameters corresponded to the inner diameter and were larger than our minimum diameter, with an average of 5.6 µm (7.1 ± 1.5 µm) (Table 1 ). In a medaka brain, Gladys et al 28 showed only medaka’s morphological features in vivo, without the delineation of the cerebral microvessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While zebrafish have only pharyngeal teeth and lack oral teeth, medaka has both oral and pharyngeal teeth Click or tap here to enter text. Regarding shape and type, there are no differences in medaka and zebrafish as both teleosts have mild heterodonty [25,26]. Meanwhile, the development of replacement teeth in the two species includes the budding of epithelium and reciprocal interaction of the mesenchyme.…”
Section: Figure 2 Image Of Zebrafish Skeleton [25]mentioning
confidence: 99%